Pemberdayaan Ibu-Ibu PKK Melalui Pelatihan Pembuatan Detergen Cair Sebagai Alternatif Penambahan Pendapatan Keluarga Desa Karang Anyar - Eva Solita Pasaribu; William Parlindungan Sihombing; Nowel Dewantara; Erbin Sitorus; Agam Sinaga; Donald Frensius Pasaribu (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
Family independence is one of the benchmarks for achieving family welfare. A prosperous family will have a positive impact on various aspects of life, one of which is the ability to meet family needs from the lowest to the highest. However, achieving family independence is not as easy as imagined. It requires a stable income and the active role of actors in the household, one of which is the mother as the primary role holder in a family. A mother's active role in various activities in the community and organizational environment is expected to improve the skills possessed. The involvement of mothers in the Family Welfare Empowerment (PKK) will open insights and creativity to further progress and development and have the initiative to increase family income. As an effort to improve the skills of PKK mothers in Karang Anyar Village, this activity provides training in making liquid detergent, based on the premise that liquid detergent is a daily family necessity and is very easy to practice independently or in groups and can be an alternative to increase family income. The final response to this activity was very positive and had an impact on the desire of PKK mothers to make it a source of additional income for the family, thus creating family independence.